Evaluation of The Ability of Bidara Leaf Extract (Zizipus mauritiana Lam.) as A Natural Preservative in Broiler Chicken Meat - M, Komaruddin; Miwada, I N.S.; Lindawati, S. A (Jurnal Peternakan Tropika, 2019)
Bidara leaf extract used in this study functions as an antibacterial. The aim of this study was to evaluate the ability of bidara leaf extract as an anti-bacterial and its effect on the characteristics ofchicken meat Broiler. This study used a completely randomized design with four treatments of bidara leaf extract material (0% (control), 10%, 15%, and 20%) and four replications. The variables observed included the value of pH, water content, water binding capacity, color, flavour, and total bacteria. The results showed that leaf extract bidara 10% to 20% can improve water binding ability (DIA) from 27.70 to 36.67; followed by a decrease in total bacteria from 2.23x10 7 to 1.1x10 7 ; with water content increasing from 76.29 to 77.99; but at pH it has decreased from 6.66 to 5.99. The conclusion of this study is that bidara leaf extract can be a natural preservative inchicken meat broiler. Keywords : bidara leaf extract, natural preservative, broiler chicken meat.